Biased political reasoning and relational inferences in a small-group deliberative context. Issue 2 (15th March 2019) - Brinker, David L.
Abstract : Theorists of deliberative democracy envision a citizenry engaged in collective reasoning about public issues on the merits of rival arguments. Partisanship undermines this ideal when it causes people to discount counter-attitudinal arguments, independent of their quality. Empirical deliberative theory lacks an account for what mechanism mitigates this bias in small-group settings. To close that theoretical gap, this study draws on Relational Framing Theory and identifies a relational component of the reasoning process. Participants rated the relevance of dominance/submission and affiliation/disaffiliation relational frames after a small-group deliberation. This perception influenced participants' decisions to endorse arguments as legitimate public reasons. Implications for deliberative theory, research, and practice are discussed.